(untitled) (Research, Society and Development, 2024)
This retrospective cohort study aimed to compare the need for dental treatment performed under general anesthesia (GA) among individuals with intellectual disabilities (ID), cerebral palsy (CP), autism spectrum disorder (ASD) or Down syndrome (DS) attended at the dental service of São Juliao’s Hospital, in Mato Grosso do Sul, Brazil. Data from 790 dental records of individuals of both sexes with special health care needs (SHCNs) and 0 to 59 years of age, who underwent treatment under GA, were collected. Patients were evaluated and divided into four groups: G1 (ID [n=321]); G2 (CP [n=285]); G3 (ASD [n=131]); and G4 (DS [n=53]). Preventive, restorative, and surgical procedures were performed in a surgery center; the stage of caries disease was assessed using the Caries Assessment Spectrum and Treatment (i.e., CAST) instrument. The chi-squared test and analysis of variance were used for comparisons, with a significance level of 5%. There was a higher percentage of males (p=0.0062) and subjects between 19 and 35 years of age (p<0.0001). The groups differed significantly (p<0.05) in terms of mean age, with G3 the youngest. Regarding the CAST instrument, subjects in G1 and G2 demonstrated a significantly higher percentage of code 7 (p<0.01 [chi-squared test]). Twelve months after the first procedure performed under GA, only 16.45% returned for a second appointment. The need for dental treatment accumulated in all four groups, with the greatest number of subjects diagnosed with ID and CP (i.e., G1 and G3, respectively).